2016
DOI: 10.1177/1073191116652227
|View full text |Cite
|
Sign up to set email alerts
|

Burdensomeness, Belongingness, and Capability: Assessing the Interpersonal–Psychological Theory of Suicide With MMPI-2-RF Scales

Abstract: Given the emerging body of literature demonstrating the validity of the interpersonal-psychological theory of suicide (IPTS), and the importance of increasing our understanding of the development of risk factors associated with suicidal behavior, it seems worthwhile both to expand IPTS research via Minnesota Multiphasic Personality Inventory-2-Restructured Form (MMPI-2-RF) correlates and to expand the availability of methods by which to assess the constructs of the IPTS. The present study attempted to do so in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 69 publications
4
30
1
1
Order By: Relevance
“…Other recent studies have demonstrated the MMPI-2-RF's promising utility in informing suicide risk assessment in accordance with modern suicide theory (Anestis et al, 2016) newly proposed suicide-specific diagnostic constructs (Rogers et al, 2017), and relevant National Institute of Mental Health Research Domain Criteria (Venables et al, 2015). Anestis et al (2016) examined associations between the MMPI-2-RF scales and Joiner's (2005) interpersonal psychological theory of suicide, an early ideationto-action theory. They found broad and narrow measures of internalizing dysfunction (e.g., EID, RCd) to be strongly associated with suicide desire, whereas measures of externalizing (BXD, RC4) were closely related to suicide capability.…”
Section: The Mmpi-2-rfmentioning
confidence: 81%
“…Other recent studies have demonstrated the MMPI-2-RF's promising utility in informing suicide risk assessment in accordance with modern suicide theory (Anestis et al, 2016) newly proposed suicide-specific diagnostic constructs (Rogers et al, 2017), and relevant National Institute of Mental Health Research Domain Criteria (Venables et al, 2015). Anestis et al (2016) examined associations between the MMPI-2-RF scales and Joiner's (2005) interpersonal psychological theory of suicide, an early ideationto-action theory. They found broad and narrow measures of internalizing dysfunction (e.g., EID, RCd) to be strongly associated with suicide desire, whereas measures of externalizing (BXD, RC4) were closely related to suicide capability.…”
Section: The Mmpi-2-rfmentioning
confidence: 81%
“…Therefore, some of the participants we included in the current study overlap with other studies. Although some of these INQ data were used in 12 other publications (Anestis et al, 2018; Chu et al, 2017b; Hagan, Podlogar, Chu, & Joiner, 2015; Hames et al, 2015; Hawkins et al, 2014; Hom, Hames, et al, 2017; Rogers et al, 2017a; Rogers et al, 2017b; Rogers et al, 2018; Rogers & Joiner, 2016, 2018; Silva, Ribeiro, & Joiner, 2015), it should be noted that our participants’ data do not overlap with those used in primary 15-item INQ validation paper (Van Orden et al, 2012). Furthermore, the analyses that we conducted are unique to the current study and provide important clinical utility information with the most up-to-date data.…”
Section: Methodsmentioning
confidence: 99%
“…The theory suggests this stable trait develops in response to lifetime exposure to painful and frightening experiences (Chu et al 2017;Joiner 2005;Van Orden et al 2010). The ITS has been tested in a range of populations (Anestis et al 2018;Bryan et al 2013;Cole et al 2013;Czyz et al 2015;Heelis et al 2016;Miller et al 2016;Wilson et al 2013;Wolford-Clevenger et al 2017) with broad support for the theory reported in a meta-analysis of 122 studies (Chu et al 2017), and its associations have under-pinned evidence-based efforts to increase identification of suicide risk (Ribeiro et al 2013) and treatments (Joiner Jr et al 2009). Our earlier study reported that, in a non-clinical sample, thwarted belonging and perceived burden were associated with suicidality and that this association was not attenuated by high levels of autistic traits (Pelton and Cassidy 2017).…”
Section: Introductionmentioning
confidence: 99%